Buku English Story sebagai Sumber Belajar Bahasa Inggris untuk Siswa SMP - Tities Hijratur Rahmah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2021)
English materials easily accessed in internet still cannot require the objectives of English subject entirely since the students only browse and read the materials of their interest. The objective of English subject is to make the students mastering in understanding English well which suits to not only the students’ interest but also the students’ english level, and a variety of material on a wide range of topics. Due to the problem stated, this study aims to describe the use English book that can be an alternative resources needed by the students nowadays. As the learning resources of English subject. The book contains the compilation of English materials for Junior High School students of Purnama Gempol.